Encapsulamento de redes de Bragg em fibra Ótica - Batista, Caroline Fernanda Lopes (2017)
This work presents the process of encapsulation of optical fiber sensors in Bragg networks for applications in temperature measurements ranging from 5 ° C to 60 ° C. Four materials for the FBG coating are proposed: Silicone, conventional Super Bonder, Super Bonder Gel and metal tube. The encapsulated sensors performance have been evaluated and the results are shown in this paper. It was possible to demonstrate that the sensitivity in the sensors is given by a linear way, that is, the higher temperatures implies longer wavelengths. Then, the longer wavelengths implies longer stabilization time and, consequently, the thermal inertia.